Research Progress on Natural Compounds Exerting an Antidepressant Effect through Anti-inflammatory - Yuan, Caixia; Yao, Yucen; Liu, Tao; Jin, Ying; Yang, Chunrong; Loh, Xian J.; Li, Zibiao (Current Medicinal Chemistry, 2022)
Depression is a common mental illness that belongs to the category of emotional disorders that causes serious damage to the health and life of patients, while inflammation is considered to be one of the important factors that cause depression. In this case, it might be important to explore the possible therapeutic approach by using natural compounds exerting an anti-inflammatory and antidepressant effect, which has not been systematically reviewed recently. Hence, this review aims to systematically sort the literature related to the mechanism of exerting an antidepressant effect through antiinflammatory actions and to summarize the related natural products in the past 20 years in terms of several inflammatory-related pathways (i.e., the protein kinase B (Akt) pathway, monoamine neurotransmitters (5-hydroxytryptamine and norepinephrine) (5-HT and NE), the nod-like receptor protein-3 (NLRP3) inflammasome, proinflammatory cytokines, neurotrophins, or cytokine-signaling pathways), which might provide a useful reference for the potential treatment of depression.
Keywords: proinflammatory cytokine